Diaspora grand-mothering in Nigeria (2022)
Leaving children in the care of grandparents is a fairly common practice in close knit societies such as Nigeria. This service of providing childcare by grandmothers is however taking a transnational form with the exportation of grandmothers from Nigeria to care for grandchildren whose parents, out of economic necessity, must work fulltime. This article explores the dynamics of Nigerian grandmothers providing childcare to grandchildren in the diaspora, using twenty-five grandmothers selected in Ibadan,Southwest Nigeria based on their experience of this phenomena. Study found that participants were motivated to undertake diaspora childcare out of empathy for the younger couples, the feeling of a sense of duty, perceived knowledge of childcare, selffulfilment, cultural norms, and the need to minimize the cost of childcare for couples in the diaspora. The sense of being ‘available’ played a significant role in participants’ decision to provide childcare abroad. The study equally showed that the practice had both emotional and social impact on the grandmothers involved. The research advances the significance of diaspora grandmother child care services as a critical part of the broader debate on companionship and gender roles in old age,especially in Africa, where elders remain key transmitters of societal norms and values.